A study on skills, strategic planning and performance of small and medium enterprises in Punjab, Pakistan - Ahmad, Israr (2021)
The study examines the determinants of companies' key skills and strategies to understand better how firms can use their resources to achieve success. This study is, therefore, undertaken for this reason to investigate the connections between possible variables. Specifically, it aims to examine the mediating effect of strategic planning on the relationship between technical skills, managerial skills, entrepreneurial skills, business skills, and performance of the small and medium enterprises in Punjab, Pakistan. In addition, all independent, dependent, and mediator variables are theoretically underpinned by the Resource-Based View (RBV) theory in view of the utilizations and implication of organizational resources. Data collected through self – administrative questionnaires with 265 owners/managers of small and medium enterprises in Punjab, Pakistan. Partial Less Squares Structural Equation Modelling (PLS-SEM) is used to analyze the data and test the hypothesis. The study's findings suggest a significant relationship between managerial skills, entrepreneurial skills, business skills, and strategic planning. Strategic planning mediating the relationship between managerial skills, entrepreneurial skills, business skills, and firm performance for the mediating effect. However, no empirical support has been found from the mediator on the relationship between technical skills and firm performance. This study provides valuable insights into strategic planning's role in improving the firms’ performance to the owners/managers of small and medium enterprises, policymakers, and researchers. SMEs’ owners/managers should also be encouraged to undertake strategic planning that can encourage them to utilize their resources to improve their performance. Finally, the study concludes with feedback from theory, methodology, consequences, guidelines, limitations, and future research.